FAKTOR YANG MEMENGARUHI IBU BEKERJA TIDAK MEMBERIKAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SINGKOHOR: Factors Affecting The Working Mother Do notgive Exclusive breast milk IN the working area singkohor kec puskesmas. Singkohor - Fitriani Bancin; Fatma Sylvana Dewi Harahap; Aida Fitria (Universitas Widya Gama Mahakam Samarinda, 2020)
Infant deaths that are infectious can be prevented by exclusive breastfeeding during the first 6 months. Although the number of mothers who have realized the importance of breastfeeding their babies has increased, it has still not been successful for women to breastfeed for up to 6 months. Indonesia Health Profile Data for 2018 shows that the percentage of exclusive breastfeeding in infants aged 0-6 months is only 61.5%. This study aimed to analyze the factors that affecting housewife not breastfeeding exclusively at Working Area of ​​the Singkohor Health Center. This type of research uses mix methods. The populations were 80 people and the sample was 5 people. The method of collecting data was through interviews with respondents using questionnaires and in-depth interviews with informants. Data analysis was using univariate, bivariate and multivariate analysis. Based on the chi-square test results obtained on the age variable with p-value = .117, education p = 0.000, knowledge p = .001, attitude p = .003, husband support p = 0.000 with the most influential factor was husband support exp (B) 892.841. Interview results showed exclusive breastfeeding was only given to children when crying alone. The conclusion shows that there was an influence between age, education, knowledge, attitude and support of the husband and housewife not exclusively breastfeeding at Singkohor Health Center and the most influential variable was husband support.